Emerging stock markets factbook 1994 - International Finance Corporation (Washington, D.C. : International Finance Corporation, 1994)
This edition of the Emerging Stock Markets Factbook is the eighth in the IFC's annual series tracking the development of equity markets in developing countries.The factbook is designed to serve as a reference for institutional investors, investments bankers, academics, economists and journalists.
aia 09/09/2016
Ref
Keywords: Stock exchanges; Stocks; Securities; International finance; Investments; Developing countries